Act of Jan. 24, 1901, ch. 144, § 18, W.Va. Acts 314, 320-21. - (:unkn) unknown (My University, 1901)
to regulate the keeping of gun powder and other inflammable or dangerous substances; to provide in or near the city places of burial of the dead, and to regulate the interment therein?"
Keywords: GUNPOWDER - STORAGE